THE IMPLEMENTATION OF GUIDED WRITING STRATEGIES FOR WRITING RECOUNT TEXT AT VIII GRADE STUDENTS IN SMP N 1 SINGARAJA IN ACADEMIC YEAR 2015/2016 - ., Kadek Era Kusuma Dewi; ., Drs. Asril Marjohan,MA; ., Kadek Sonia Piscayanti, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk meningkatkan kemampuan siswa dalam menulis recount text dengan menggunakan Guided Writing in the form of Chained Story. Tujuan utama dalam penilitian ini adalah meningkatkan kemampuan siswa dalam menulis terutama dalam isi, organisasi, kosa kata, tata bahasa, dan mekanik. Jenis penelitian ini merupakan Penelitian Tindakan Kelas (PTK) dengan siswa dari SMPN 1 Busungbiu dan sasaran dalam penelitian ini merupakan siswa kelas VIIIB4. Penelitian ini meliputi 2 siklus dimana setiap siklus terdiri dari empat pertemuan. Hasil dari pre-test dan post-test akan dianalisis dan dibandingkan diakhir siklus. Hasil penelitian ini menyatakan bahwa kemampuan siswa dalam menulis recoun text bisa ditingkatkan melalui penggunaan Guided Writing in the form of Chained Story. Mereka mendapat 54.4% (rendah) di pre-test, setelah itu mereka mendapat 66.4% (sedang) in siklus I, dan terkahir, pencapain mereka 77.9% (baik) di siklus II. Kata Kunci : Menulis, Teks Recount, Panduan Menulis, Cerita Berantai This study aimed at improving the students’ ability in writing a recount text by using Guided Writing in the form of Chained Story. It particularly aimed at improving the students’ ability in writing especially in the content, organization, vocabulary, grammar, and mechanic. This study was designed in the form of a classroom action-based research with the second year students of SMP N 1 Busungbiu at class VIIIB4 as the subject of this study. Two cycles were covered in this study in which each cycle comprised four sessions. The result of the pre-test and post-test which was conducted at the end of each cycle were analyzed and compared. The result of the study revealed that the students’ ability in writing a recount text could be improved through the use Guided Writing in the form of Chained Story. It could be seen from the increase of the students’ mean score. They got 54.4% (poor) in the pre-test, then they gained 66.4% (moderate) in cycle I, and at last, they achieved 77.9% (good) in cycle II. keyword : Writing, recount text, guided writing, chained story